Imaging Based Methods of Liver Fibrosis Assessment in Viral Hepatitis: A Practical Approach - Khallafi, Hicham; Qureshi, Kamran (Interdisciplinary Perspectives on Infectious Diseases, 2015)
Liver fibrosis represents the repair mechanism in liver injury and is a feature of most chronic liver diseases. The degree of liver fibrosis in chronic viral hepatitis infections has major clinical implications and presence of advanced fibrosis or cirrhosis determines prognosis. Treatment initiation for viral hepatitis is indicated in most cases of advanced liver fibrosis and diagnosis of cirrhosis entails hepatology evaluation for specialized clinical care. Liver biopsy is an invasive technique and has been the standard of care of fibrosis assessment for years; however, it has several limitations and procedure related complications. Recently, several methods of noninvasive assessment of liver fibrosis have been developed which require either serologic testing or imaging of liver. Imaging based noninvasive techniques are reviewed here and their clinical use is described. Some of the imaging based tests are becoming widely available, and collectively they are shown to be superior to liver biopsy in important aspects. Clinical utilization of these methods requires understanding of performance and quality related parameters which can affect the results and provide wrong assessment of the extent of liver fibrosis. Familiarity with the strengths and weaknesses of each modality is needed to correctly interpret the results in appropriate clinical context.